Collectivism-Individualism dan Prosocial Behavior Pada Remaja - Zahroh, Fatimatus (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2023)
Prosocial behavior is a form of behavior that is present in social interaction through actions designed to help others regardless of the basic intent of doing the help. Currently, millennial youth in the digital era have low prosocial behavior that tends to be lazy to help others in their surroundings. One of the factors that influence prosocial behavior is collectivism – individualism in adolescents. The research was conducted with the aim of knowing the relationship between collectivism-individualism and prosocial behavior in adolescents, the relationship between collectivism and prosocial behavior in adolescents, and the relationship between individualism and prosocial behavior in adolescents. The research was conducted using quantitative research methods with a correlational approach in order to find out the variation of one or more variables based on the correlation coefficient. The results of the research conducted show that there is a positive and significant relationship between collectivism-individualism and prosocial behavior in adolescents. so, this dal shows that the higher the collectivism-individualism, the higher the prosocial behavior of individuals and it is said that there is a relationship between the two. A positive and significant relationship was also generated between individualism and prosocial behavior, but collectivism did not have a significant relationship with prosocial behavior. High or low collectivism cultural values do not affect social behavior. Prososial behavior merupakan bentuk perilaku yang hadir dalam interaksi sosial melalui tindakan yang direncanakan untuk menolong orang lain tanpa memerdulikan maskud dasar dilakukannya pertolongan. Saat ini, remaja milenial di era digital memiliki perilaku propososial yang rendah higga cenderung malas untuk menolong sesama pada lingkungan sekitarnya. Faktor yang mempengaruhi perilaku prososial salah satunya adalah collectivism – individualism pada remaja. Penelitian dilakukan dengan tujuan untuk mengetahui bagaimana hubungan antara collectivism-individualism dengan prosocial behavior pada remaja, hubungan collectivism dengan prosocial behavior pada remaja, dan hubungan antara individualism dengan prosocial behavior pada remaja. Penelitian dilakukan dengan menggunakan metode penelitian kuantitatif dengan pendekatan korelasional agar mengetahui variasi dari satu atau lebih variabel berdasarkan koefisien korelasi. Hasil dari penelitian yang dilakukan menunjukkan bahwa adanya hubungan secara positif serta signifikan antara collectivism-individualism dan prosocial behavior pada remaja. sehingga, hal tersebut menunjukkan bahwa semakin tinggi collectivism-individualism maka akan semakin tinggi perilaku prososial pada individu dan dikatakan bahwa terdapat hubungan diantara keduanya. Hubungan positif dan signifikan juga dihasilkan antara individualism dan prosocial behavior, tetapi untuk collecitivism tidak memiliki hubungan secara signifikan dengan prosocial behavior. Tinggi rendahnya nilai budaya collectivism tidak mempengaruhi perilaku sosial.